Building up a dairy herd in Kansas - Clark, C. H. (My University, 1902)
Introduction: When we review the dairy interests of Kansas, noting the improved methods of the cheese factory, the skimming station and the creamery, and the increasing demand for milk in our cities, we turn naturally to the source of the raw material and inquire as to its permanence and whether it is equal to the demands made upon it. We all know that the cow, as a source of milk supply to the human race, is something of an abnormal creature, made possible only by a long and careful process of feeding, breeding, selection and milking, and that without due precautions she will gradually drift back to the natural conditions of giving only milk enough to supply the needs of her offspring. The possibility of not only maintaining the present high standard, but of further, and more rapid and wide spread improvement is clearly shown when we consider what has already been done under conditions less favorable than now exist. The Holstein-Friesian, Jersey, Guernsey and Ayrshire herds have become famous as milk producers, though many of the breeders of these cattle know little or nothing of the foundation principles of breeding, feeding and variation. They lacked the stimulus that has been given by the Babcock test and the invention of modern dairy machinery and methods. Knowledge was not so easily obtained as at present. There was no improved stock with which the early breeders could cross their common stock, for all cattle were wild originally. The dawn of the twentieth century certainly offers great encouragement to those who wish to continue the work so well begun.
Citation: Clark, C. H. Building up a dairy herd in Kansas. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Dairy Herd; Kansas; Animal Husbandry; Theses